2021
DOI: 10.3389/fimmu.2021.700152
|View full text |Cite
|
Sign up to set email alerts
|

Single-Cell Transcriptomic Profiling of MAIT Cells in Patients With COVID-19

Abstract: BackgroundMucosal-associated invariant T (MAIT) cells are considered to participate of the host immune response against acute severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection; however, single-cell transcriptomic profiling of MAIT cells in patients with COVID-19 remains unexplored.MethodsWe performed single-cell RNA sequencing analyses on peripheral MAIT cells from 13 patients with COVID-19 and 5 healthy donors. The transcriptional profiles of MAIT cells, together with assembled T-cell rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 38 publications
3
20
0
Order By: Relevance
“…Homing of MAIT cells to inflamed tissues, as evidenced by high expression of chemokine receptors, and activation-induced cell death may contribute to the decrease in circulating MAIT cells. In patients with COVID-19, the frequency of pyroptotic MAIT cells rather than apoptotic MAIT cells is significantly increased, suggesting that activated MAIT cells may exhibit different forms of morbidity ( 61 ). Furthermore, a previous study has shown that the CD3 + MR1-tetramer + MAIT cell frequency is similar in HCs and patients with RA and that CD161 is reduced in early RA patients, indicating that the gating strategy of CD3 + CD161 + Vα7.2 + might be partially responsible for the reduction in MAIT cells ( 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…Homing of MAIT cells to inflamed tissues, as evidenced by high expression of chemokine receptors, and activation-induced cell death may contribute to the decrease in circulating MAIT cells. In patients with COVID-19, the frequency of pyroptotic MAIT cells rather than apoptotic MAIT cells is significantly increased, suggesting that activated MAIT cells may exhibit different forms of morbidity ( 61 ). Furthermore, a previous study has shown that the CD3 + MR1-tetramer + MAIT cell frequency is similar in HCs and patients with RA and that CD161 is reduced in early RA patients, indicating that the gating strategy of CD3 + CD161 + Vα7.2 + might be partially responsible for the reduction in MAIT cells ( 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that host responses to SARS-CoV-2 are dependent on viral load and infection time course, with observed differences due to age and sex that may contribute to disease severity [13]. In severe COVID-19 patients, differentially expressed genes are enriched with adaptive cellular and humoral immune responses, cell cytotoxicity, chemotaxis, and apoptosis compared with those in moderate cases [24]. In summary, altered expression of genes might play important role in COVID-19 in IFN response, although remains debated.…”
Section: Molecular Pathogenesis Of Covid-19mentioning
confidence: 99%
“…Sc-RNA-seq analysis revealed a depletion of MAIT cells in patients with severe disease even if the number of clonotypes of MAIT cells was relatively high. Moreover, there were more large clonal expansions (clonal size > 10) in the severe cases than in the other conditions [50].…”
Section: Maitmentioning
confidence: 84%
“…Complex analyses were performed on blood by Flow cytometry (7/11 papers) and Sc-RNA-seq (8/11 papers) and on serum analyzed by Luminex or ELISA. Flow cytometry analysis showed that reduction of MAIT cells was significant in severe COVID-19 patients compared to healthy controls [39,40,43,46,[48][49][50][51][52][53] and compared to HCs or infected patients. In convalescent patients, MAIT cell frequency did not significantly increase.…”
Section: Maitmentioning
confidence: 98%